Arbuscular mycorrhizal symbiosis of Viola baoshanensis at Baoshan Pb/Zn mine in China - Zhong, Weiliang (Journal of Environmental Engineering and Landscape Management, 2024)
Despite great potential for arbuscular mycorrhizal fungi (AMF) in restoration of heavy metals (HMs) polluted lands, limited information is available about the arbuscular mycorrhizal (AM) symbiosis of naturally-occurring hyperaccumulators. A preliminary survey was conducted to investigate the AM symbiosis of Viola baoshanensis, a Cadmium (Cd) hyperaccumulator, growing at an abandoned mine. Shoot/root ratios of 1.78 for Cd, and 2.57 for zinc (Zn) indicate that these two metals were preferentially transported from roots to shoots, whereas the ratio of 0.32 for lead (Pb) shows that most Pb was stored in roots. High level of colonization was found in the roots of V. baoshanensis with relative mycorrhizal root length of 69.1%, relative arbuscular richness of 46.9% and relative vesicular richness of 1.7%. Fifteen AMF species were identified from the root zone soil of V. baoshanensis. The dominant AMF genus was Glomus, and the most abundant species were Glomus ambisporum and Claroideglomus etunicatum.